2018
DOI: 10.1155/2018/1784821
|View full text |Cite
|
Sign up to set email alerts
|

Dedolomitization Potential of Fluids from Gypsum-to-Anhydrite Conversion: Mass Balance Constraints from the Late Permian Zechstein-2-Carbonates in NW Germany

Abstract: The Zechstein-2-Carbonates represent one of the most prolific hydrocarbon systems of Central Europe. Carbonate reservoir quality is primarily controlled by mineralogy, with dolomite representing moderate-to-good porosities and calcite commonly representing low porosities. Current models suggest that this calcite is the result of a basin-wide phase of dedolomitization. The calcium (Ca) source for the dedolomites is thought to be derived from the fluids liberated during gypsum-to-anhydrite conversion. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The influx of calcitising fluids into the Ca2 after dolomitisation caused widespread calcitisation, which had significant impact on influencing reservoir quality (Schoenherr et al, 2018). Hallenberger et al (2018) recently focused on unravelling the origin of these calcitising fluids and estimated mass balance constraints, determining that calcitising fluid generated during gypsum -anhydrite dehydration would only account for <1% of slope calcitisation in the Ca2. Schoenherr et al (2018) indicates that pressure solution of the surrounding anhydrite beds is likely to be the dominant source of calcitising fluids.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The influx of calcitising fluids into the Ca2 after dolomitisation caused widespread calcitisation, which had significant impact on influencing reservoir quality (Schoenherr et al, 2018). Hallenberger et al (2018) recently focused on unravelling the origin of these calcitising fluids and estimated mass balance constraints, determining that calcitising fluid generated during gypsum -anhydrite dehydration would only account for <1% of slope calcitisation in the Ca2. Schoenherr et al (2018) indicates that pressure solution of the surrounding anhydrite beds is likely to be the dominant source of calcitising fluids.…”
Section: Geological Settingmentioning
confidence: 99%
“…Love et al (1997) suggested that the extent of calcitisation was facies-independent and instead predominantly influenced by proximity to feeding faults. Due to the extensive calcitisation of the dolomite matrix observed in the studied wells and across the Ca2 slope deposits (Schoenherr et al, 2018), the source of the Ca-rich fluids are dominantly associated with pressure solution of the surrounding A1 and A2 anhydrite units (Hallenberger et al, 2018;Schoenherr et al, 2018). Calcitisation operates in a shallow burial diagenetic environment where fractures, which are acting as conduits for calcitising fluids, are equally of shallow burial (mesogenetic) origin as the basin continuously subsides.…”
Section: Stylolitisation and Calcitisation During Intermediate Burialmentioning
confidence: 99%
“…However, numerous studies have also shown an enhancement of reservoir quality by dedolomitization (e.g., Schmidt 1965;Evamy 1967;Braun and Friedman 1970;Frank 1981;Qin and Yang 1997). Theoretically, 12.9% void volume will be produced by the dolomitization reaction involving 1 mol of dolomite (64.4 cm 3 ), which is 12.9% less than 2 mol of calcite by volume (73.9 cm 3 ) ((73.9-64.4)/73.9*100%) (Ayora et al 1998;Hallenberger et al 2018). The reservoir quality of dolostones is therefore significantly higher than that of limestones, such as in the Feixianguan Formation in the Sichuan Basin (Jiang et al 2018) and the Ordovician carbonate in the Tazhong area of the Tarim Basin (Jia et al 2016).…”
Section: Impact On Reservoir Qualitymentioning
confidence: 99%
“…Dedolomitization can be controlled by several factors, such as the Ca 2+ /Mg 2+ ratio in the diagenetic fluid (Khalaf and Abdal 1993), dolomite stoichiometry (Nader et al 2008), CO 2 partial pressure (De Groot 1967;Clark 1980;Hallenberger et al 2018), temperature and salinity (Hardie 1967;Hallenberger et al 2018) and the degree of fracture development (Al-Hashimi and Hemingway 1973;Budai et al 1984;Zeeh et al 2000;Reuning et al 2009). The major factors that control dedolomitization in the Majiagou Formation are discussed in this study to provide further insight into the dedolomitization process.…”
Section: Introductionmentioning
confidence: 99%
“…The floor and roof anhydrites originally were deposited as gypsum [17]. Up to 40 vol% of structural bound water is expelled during recrystallization from gypsum to anhydrite, which likely takes place in burial depth of less than 250 m [49,50]. The escaping water is oversaturated with respect to CaSO 4 [51] and might have led to a second pulse of anhydrite cementation and replacement during shallow burial.…”
Section: Diagenetic Productsmentioning
confidence: 99%